2022
DOI: 10.1097/cm9.0000000000001873
|View full text |Cite
|
Sign up to set email alerts
|

Clinical application of Shenton's line to determine the femoral artery bifurcation using the antegrade common femoral artery approach

Abstract: To the Editor: The common femoral artery is the most popular puncture access route for surgical intervention. The distal end of the common femoral artery where the deep femoral artery and the superficial femoral artery bifurcate is difficult to identify, especially when vascular surgeons perform antegrade femoral artery puncture to treat ipsilateral lower extremity artery disease. Many studies have reported methods to anatomically localize the femoral head on the X-ray. Here, we introduce an anatomic landmark,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
(4 reference statements)
1
0
0
Order By: Relevance
“…Similarly, through a single-center review of computed tomography angiography studies from China, the authors showed that the femoral artery bifurcation was frequently below the midpoint of the femoral head and above the Shenton’s line, an imaginary line drawn along the inferior border of the superior pubic ramus and along the inferomedial border of the neck of the femur. 14 These results are similar to our data, showing that access below the radiographic midpoint of the femoral head would avoid the inguinal ligament and the femoral artery bifurcation in over 80% of cases. Importantly, over one-half the cohort had a >25% overlap of either the inguinal ligament or the femoral artery bifurcation over the femoral head, suggesting that imaging strategies used to visualize the bony landmarks alone might not be sufficient for safe femoral access.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, through a single-center review of computed tomography angiography studies from China, the authors showed that the femoral artery bifurcation was frequently below the midpoint of the femoral head and above the Shenton’s line, an imaginary line drawn along the inferior border of the superior pubic ramus and along the inferomedial border of the neck of the femur. 14 These results are similar to our data, showing that access below the radiographic midpoint of the femoral head would avoid the inguinal ligament and the femoral artery bifurcation in over 80% of cases. Importantly, over one-half the cohort had a >25% overlap of either the inguinal ligament or the femoral artery bifurcation over the femoral head, suggesting that imaging strategies used to visualize the bony landmarks alone might not be sufficient for safe femoral access.…”
Section: Discussionsupporting
confidence: 92%